The Influence of Organizational Culture, Problem-Solving Ability, and Work Motivation on Labor Performance at Jambi University - Devie Novallyan; Martinis Yamin; Risnita Risnita (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2025)
This study aims to describe and analyze the magnitude of the direct and indirect influence of the effectiveness of organizational culture, laboratory assistant problem-solving ability, and Motivation on laboratory assistant performance. The study used a quantitative approach with a survey design. The population of lecturers was 608 and laboratory assistants 15, while the sample of lecturers 132 and laboratory assistants 15 were taken by purposive sampling. Data was collected through a Likert scale questionnaire, which was then analyzed using path analysis. The study's results showed that: 1) organizational culture directly affects laboratory assistant performance. This can be seen from the significance value of 0.000 <0.05. In addition, the t_count value = 11.254 > t_table = 1.970; 2) laboratory assistant problem-solving ability directly affects laboratory assistant performance. This can be seen from the significance value of 0.045 <0.05. In addition, the t_count value = 2.224 > t_table = 1.970; 3) The laboratory assistant's Motivation directly affects the laboratory assistant's performance. This can be seen from the significance value of 0.034 <0.05. In addition, the t_count value = 2.366 > t_table = 1.970; 4) Organizational Culture and the laboratory assistant's problem-solving ability simultaneously affect the laboratory assistant's performance. This can be seen from the significance of 0.031 <0.05; 5) There is a simultaneous influence of Organizational Culture and Motivation on the performance of the laboratory assistant, this can be seen from the significance value of 0.023 <0.05; 6) There is no simultaneous influence of the problem-solving ability of the laboratory assistant and Motivation on the performance of the laboratory assistant, this can be seen from the significance value of 0.116 > 0.05; 7) the problem-solving ability of the laboratory assistant has a direct effect on the work motivation of the laboratory assistant, this can be seen from the significance value of 0.000 <0.05. In addition, the t_count value = 10.595 > t_table = 1.970; 8) Organizational Culture does not have a positive effect on Motivation. This can be seen from the significance value of 0.252 > 0.05. In addition, the t_count value = -1.199 < t_table = 1.970; 9) There is a simultaneous influence of Organizational Culture and the problem-solving ability of laboratory assistants on Motivation, this can be seen from the significance of 0.00 < 0.05; 10) There is a simultaneous influence of Organizational Culture, problem-solving ability of laboratory assistants and Motivation on Laboratory Assistant Performance. This can be seen from the significance of 0.050 = 0.05.These results provide the conclusion that organizational culture, laboratory assistant problem-solving ability and Motivation have a direct and simultaneous effect on laboratory assistant performance.